The Chronicle of Digital (Media) Arts in Contemporary Indonesia: The Shifting of Focus Toward Society 5.0 - Kristiyono, Jokhanan; Ida, Rachmah; Ida Bagus, Wirawan; Mayastuti, Mayastuti (Technium Social Sciences Journal, 2022)
This article describes the advances in the genealogy of digital media art in Indonesia. The evolution of digital art or works of digital art is inseparable from the growth of the art itself. This article chronologically describes the development of art in Indonesia, from the starting point of the advancement of art in the Dutch colonial era to digital art. The method used in this study is a digital meta-analysis with an exploratory qualitative approach-data collection technology by observing digital metadata to develop media and participatory art in the Indonesian art community. The result is technology-based art (digital art). This article is the essential concept and idea of today’s digital artists, with works of art not just produced in the platform or digital format. Creating a work of art using the concept of digital thinking as a form of artistic appreciation is the basis for making a digital work of art. Digital media art is the foundation of thinking, thinking, and interaction. This modern society is shifting toward society 5.0. In conclusion, the development of the Indonesian digital art community resulted in an extraordinary digital revolution in Indonesia. By placing ’digital’ and ’revolution’ into a critical perspective. The digital artist community continues to produce technology-based artworks to communicate their work to the public by holding art exhibitions for Indonesian artists as a collective social movement with digital platforms.